Teach yourself visually bridge - Galt, David (Wiley Pub., 2007)
Tricks. Trumps. Auctions. Contracts. Bridge is a challenging game, but you can quickly grasp its basics with this guide that shows how it's played. Teach Yourself VISUALLY Bridge covers everything from evaluating a hand and bidding it through playing the cards and scoring the results—guiding you play by play and trick by trick. With this book and with practice as declarer or defender, you'll quickly be playing your bridge cards right. Maybe you'll even make a slam—doubled, redoubled, and vulnerable.